2017
DOI: 10.22463/25909215.1316
|View full text |Cite
|
Sign up to set email alerts
|

Obstáculos epistemológicos sobre los conceptos de límite y continuidad en cursos de cálculo diferencial en programas de ingeniería

Abstract: ResumenEl objetivo de este trabajo fue identificar los obstáculos epistemológicos sobre los conceptos de límite y continuidad que presentan los estudiantes de programas de la Facultad de Ingeniería al inicio del proceso de formación académica en una universidad pública. Se diseñó un instrumento que incorpora una serie de actividades que utilizan diversos registros de representación semiótica tendientes a determinar el nivel de apropiación que poseen los estudiantes alrededor de los conceptos de límite y contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…They worked with a sample of 20 teachers from the math area of the Barranquilla District, 46 students from the sixth grade of the District Educational Institution for the development of Human Talent, from which the experimental group and the control group were chosen, with 23 students each, his age varies from 10 to 12 years. In their conclusions they established the importance of the development of mathematical competencies, when linked to communication and representation, as a starting point to understand, interpret and pose mathematical models that lead to solve problems, coinciding with the results mentioned in the research of Hernández-Suárez, Prada-Núñez and Ramírez-Leal (2017). On the other hand, research was found that sought to analyze the teaching work of teachers of the Bachelor of Mathematics at the Universidad Pedagógica y Tecnológica de Colombia (UPTC) as an initial step to improve classroom practices, as is the case of Leguizamón ( 2016), who worked with a sample of three teachers of the Bachelor of Mathematics under an Ontosemiotic Approach to Cognition and Mathematical Instruction.…”
Section: Mathematical Processessupporting
confidence: 56%
“…They worked with a sample of 20 teachers from the math area of the Barranquilla District, 46 students from the sixth grade of the District Educational Institution for the development of Human Talent, from which the experimental group and the control group were chosen, with 23 students each, his age varies from 10 to 12 years. In their conclusions they established the importance of the development of mathematical competencies, when linked to communication and representation, as a starting point to understand, interpret and pose mathematical models that lead to solve problems, coinciding with the results mentioned in the research of Hernández-Suárez, Prada-Núñez and Ramírez-Leal (2017). On the other hand, research was found that sought to analyze the teaching work of teachers of the Bachelor of Mathematics at the Universidad Pedagógica y Tecnológica de Colombia (UPTC) as an initial step to improve classroom practices, as is the case of Leguizamón ( 2016), who worked with a sample of three teachers of the Bachelor of Mathematics under an Ontosemiotic Approach to Cognition and Mathematical Instruction.…”
Section: Mathematical Processessupporting
confidence: 56%
“…Nevertheless, limits are never covered in any comprehensive, detailed way; instead, they are frequently introduced to move on to differentiation and then used when needed to introduce various other components of single or multivariable calculus, mostly using exercises but not problems. Along the same lines, [30] indicate that the activities carried out in the classroom influence how students understand and solve problems; added to this is the importance of registers of semiotic representation in the teaching of calculus, whose lack of various types of registers becomes an epistemological obstacle.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…En cualquier área del conocimiento, las prácticas pedagógicas deben atender tres campos esenciales inherentes al proceso educativo. Al respecto, cabe destacar que se parte del conocimiento (dimensión epistemológica) que posee el docente en relación con el área de dominio (Hernández, Prada & Ramírez, 2017), de las prácticas que enfatizan los enfoques de aprendizaje (dimensión pedagógica) por medo de las cuales los docentes valoran la actuación del estudiante, y del desarrollo de estrategias (dimensión didáctica) para lograr la correspondencia entre los procesos de enseñanza y aprendizaje (Hernández, Prada & Gamboa, 2019).…”
Section: Introductionunclassified